SPE Annual Technical Conference and Exhibition 2009
DOI: 10.2118/124277-ms
|View full text |Cite
|
Sign up to set email alerts
|

Oil Recovery by Low Salinity Brine Injection: Laboratory Results on Outcrop and Reservoir Cores

Abstract: Over the last 10 years, the emerging EOR process by injection of low salinity water has been investigated through numerous laboratories and some field tests. Extensive research programs have been launched by different teams, aiming at better understanding the involved mechanisms (clay release, cation exchange). One of the main issues is to explain the observed dispersion in additional oil recoveries. In this study, we integrate new experimental observations to the literature to carry out a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 15 publications
3
29
1
Order By: Relevance
“…However, they cannot explain all of the results. The purpose of this section is to discuss these limitations in order to stress that more careful studies are needed and to agree with the assessment in the literature that no one mechanism can explain all of the results [38,12].…”
Section: Limitations Of Dle and The Chemical Mechanismsmentioning
confidence: 89%
“…However, they cannot explain all of the results. The purpose of this section is to discuss these limitations in order to stress that more careful studies are needed and to agree with the assessment in the literature that no one mechanism can explain all of the results [38,12].…”
Section: Limitations Of Dle and The Chemical Mechanismsmentioning
confidence: 89%
“…The additional oil recovery in cases of 500-1000 mD Berea sandstone cores was attributed to the presence of kaolinite in the cores by other authors as well (Morrow and Buckley 2011). However, the reviewed literature also reports LSWF benefits for sandstone core material containing other types of clays such as illite, mica, muscovite chlorite but no kaolinite (Boussour et al 2009;Cissokho et al 2010). Note though that the (positive) response to LSWF in kaolinite free cores is somewhat delayed in comparison with those containing kaolinite.…”
Section: Range Of Residual Oil Saturationsmentioning
confidence: 95%
“…Note though that the (positive) response to LSWF in kaolinite free cores is somewhat delayed in comparison with those containing kaolinite. These observations lead Boussour et al (2009) to conclude that the presence of kaolinite is not a necessary condition for increasing oil recovery by LSWF.…”
Section: Range Of Residual Oil Saturationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that context, it was shown that flooding sandstone reservoirs with low salinity water could result in additional oil yield [6][7][8]. However, the mechanisms associated with this technique are not fully understood and all those postulated in the literature are still prone to debate [9]. Most likely, the explanation for additional oil recovery is linked to wettability modifications in sandstone reservoirs.…”
Section: Introductionmentioning
confidence: 99%